The Acting Chair's Summing Up Review of the Fund's Policy on Multiple Currency Practices-Proposals for Reform Executive Board Meeting July 1, 2022. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2022)
Executive Directors welcomed the opportunity to complete the review of the Fund's Policy on Multiple Currency Practices (MCPs). They observed that MCPs can be distortionary, create unfair competitive advantage among countries, and hamper trade and investment, particularly over the medium and long term. They agreed that the MCP policy should remain a cornerstone of the Fund's legal and policy framework to ensure orderly exchange arrangements and a stable system of exchange rates. They welcomed the adjustments to the policy to reflect developments since the last review in the 1980s so that it does not discourage good practices in FX markets and is better aligned with the Fund's other policies (including the policy on exchange restrictions and the Institutional View on the Liberalization and Management of Capital Flows (IV)), while ensuring that it continues to address policy actions that are considered impermissible under the new policy.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Foreign Exchange; Monetary Policy; Political Economy